Degradative succession of the insects in small rodents in subtropical systems (Research, Society and Development, 2022)
We evaluated the insect succession in small rodent carcasses on the soil extracts (surface vs. buried) in two areas (riparian vs. agricultural) and two seasonal periods (spring vs. summer). Daily, the rodent carcasses were weighed and the insects present were collected in them for counting and family level identification. We also measured the air and soil temperature daily, in addition to the physical and chemical characteristics of the soil. The total of 11,059 individuals from 28 taxa was collected. The most abundant taxa were Calliphoridae (70%), Formicidae (20%), Muscidae (2%), and Sarcophagidae (2%). Insect richness was higher in spring in riparian vegetation areas; however, decomposition and insect abundance were greater in spring in agricultural areas by the high temperature measured. Vespidae, Sarcophagidae, Muscidae, and Calliphoridae decreased over time with abundance peaks respectively at 3, 7, 7, and 8 days in riparian vegetation areas. Calliphoridae decreased abundance over time with a peak at five days, but Armadillidiidae increased with peak at 6-9 days in agricultural areas. Decay and insect abundance was high in agricultural areas, mainly on the soil surface. Insect richness was high in riparian vegetation areas, especially on the soil surface. Only the superficial layers of soil presented taxon indicators and all decreased over time with abundance peaks of Calliphoridae, Sarcophagidae, and Muscidae at 5-8, 7, and 7 days, respectively. This abundance peak of insect families help to understand the degradative succession of the insect community in small rodents in subtropical systems of the neotropical region.